Recognition of altered segments in Brazilian Sign Language - Verdu, Ana Claudia Moreira Almeida [UNESP]; Caneguim, Janaína de Fátima Castro; Rose, Júlio César Coelho de; Bandini, Heloisa Helena Motta (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), 2012)
The purpose of this study was to verify discriminative control by segments of signs in adolescents with deafness who use Brazilian Sign Language (BSL). Four adolescent with bilateral deafness, with 3 years of BSL teaching, saw a video presenting a children's tale in BSL. After showing accurate understanding of the story, participants saw another video of the same story with 12 signs altered in one of their segments (hand configuration, place of articulation, or movement). They apparently did not detect the alterations. However, when the signs were presented in isolation in a matching-to-sample test, they virtually always selected the picture corresponding to the unaltered signs. Three participants selected an unfamiliar picture in 50% or more trials with an altered sign as a sample, showing that they could detect the majority of the altered signs.
Keywords: Discrimination; Segments of signs; Brazilian Sign Language; Adolescents